A Longitudinal Examination of Hope and Optimism and Their Role in Type 1 Diabetes in Youths. (30th November 2015) - Van Allen, Jason; Steele, Ric G.; Nelson, Michael B.; Peugh, James; Egan, Anna; Clements, Mark; Patton, Susana R.
Abstract : Objectives To test the longitudinal associations between hope and optimism and health outcomes (i.e., HbA1c and self-monitored blood glucose [SMBG]) among youths with Type 1 diabetes mellitus (T1DM) over a 6-month period. Methods A total of 110 participants (aged 10–16 years) completed study measures at Time 1, and 81 completed measures at Time 2. Analyses examined hope and optimism as predictors of change in health outcomes, and examined SMBG as a mediator of the relationship between hope and optimism, and HbA1c. Results Change in hope, but not optimism, was associated with change in SMBG and HbA1c. Change in SMBG mediated the relationship between change in hope and HbA1c, but not between optimism and HbA1c. Conclusions It may be beneficial to assess hope in pediatric T1DM patients to identify youths who may be at risk for poor diabetes management, and to test the benefit of hope-based intervention efforts in clinical studies.